Money in Great Britain and Ireland - Josset, C. R. (Newton Abbot : David and Charles, 1971)
The book attempts to relate to the history of money in Britain from the iron rings and bars of Caesar's time to the latest coins of Elizabeth II's reign. It relates this history in a simple non-technical language, at the same time providing an essential background of political history.
Includes bibliographical references: p. [268]-270 and index.
usc 03/08/2017
Loans
Keywords: Money; Great Britain; Ireland